Male genitourinary reconstruction and trauma - Breyer, Benjamin N.; Osterberg, E. Charles (Translational Andrology and Urology, 2018)
On behalf of all the contributing authors, we are excited to extend this focused issue in Translational Andrology and Urology (TAU) on new updates in male genitourinary (GU) reconstruction and trauma.